2021
DOI: 10.31579/2578-8868/161
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Cognition and Educational Attainment as a Result of Integrating Music into Science Teaching in Elementary School

Abstract: BACKGROUND AND OBJECTIVE: This study examines the effect on third-grade students’ academic achievement and their pleasure and interest in lessons as a result of the incorporation of music into science classes. MATERIAL AND METHODS: Sixty third grade Arab school children were studied before and after listing a Mozart Concerto. Their pleasure and interest in the lesson was evaluated using the 20-statement Barak questionnaire. Comparison was made between an initial 6 lessons without music and subsequent 6 lesson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Furthermore, the study suggests that changing the type of Fortnite computer game to a thought-provoking and challenging game such as Solitaire has a similar effect to the combination of music during the learning process. Previous studies have shown that music can improve gamma waves associated with thinking and alpha waves associated with calmness and reward systems [13]. Thinking and challenging games may stimulate and increase the activity of gamma waves responsible for thinking processes, focus, and problem solving.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study suggests that changing the type of Fortnite computer game to a thought-provoking and challenging game such as Solitaire has a similar effect to the combination of music during the learning process. Previous studies have shown that music can improve gamma waves associated with thinking and alpha waves associated with calmness and reward systems [13]. Thinking and challenging games may stimulate and increase the activity of gamma waves responsible for thinking processes, focus, and problem solving.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that 10 minutes of effortless walking before class consistently improved concentration, recall and higher order thinking compared to no exercise or strenuous exercise. Complementary research has identified that various activities, including physical movement, musical engagement, adherence to a Mediterranean diet, and interactive computer games, are associated with enhanced scholastic performance (referenced in studies 18,21,22,23). These results suggest that incorporating regular periods of aerobic exercise into the school routine could be instrumental in boosting academic learning outcomes (as supported by references 1,18,21,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Complementary research has identified that various activities, including physical movement, musical engagement, adherence to a Mediterranean diet, and interactive computer games, are associated with enhanced scholastic performance (referenced in studies 18,21,22,23). These results suggest that incorporating regular periods of aerobic exercise into the school routine could be instrumental in boosting academic learning outcomes (as supported by references 1,18,21,22,23). Such an intervention offers a cost-effective and relatively straightforward strategy with the potential for significantly amplifying educational achievement.…”
Section: Discussionmentioning
confidence: 99%
“…然而, 一些研究并未发现莫扎特效应 (Giannouli et al, 2019;Standing et al, 2008;Steele et al, 1997) Padulo et al, 2020;Rauscher et al, 1993;Smith et al, 2010)。同时, 认知神经学的证据支持莫扎特音乐 会对特定大脑活动产生独特的影响 (Jausovec & Habe, 2004;Rideout & Laubach, 1996;Verrusio et al, 2015;Zhu et al, 2008), 如听莫扎特音乐降低了被 试的脑电活动并提高了认知表现 (Jausovec et al, 2006), 增强健康老年人和儿童的 α 节律活动 (Mualem et al, 2021), 使 P3a 和 P3b 的波幅和潜伏期发生改 变等 (Zhu et al, 2008)。然而不少研究未能发现莫 扎特音乐对时空推理能力的促进作用 (Borella et al, 2017;Crncec et al, 2006;Steele, Bass et al, 1999), (Steele, Bella et al, 1999)Lints & Gadbois, 2003), 在控制唤醒 之后, 莫扎特音乐的优势便消失了 (Thompson et al, 2001); 同时, 聆听愉悦的音乐可以促进多巴胺的 释放 (Nadler et al, 2010), 从而促进认知表现、强 化学习 (Gold et al, 2013) et al, 1985;Voyer et al, 1995), 这一 优势甚至早在婴儿时期就已经很明显 (Moore & Johnson, 2008;Quinn & Liben, 2008),…”
unclassified